What are the relative merits of interventions used to reduce the occurrences of disruptive vocalisation in persons with dementia? – a systematic review. (29th June 2015) - Randall, Edward W; Clissett, Philip C
Abstract : Introduction: Dementia is a major health issue, and many people who have the progressive disease express disruptive vocalisation. These behaviours place large burdens on carers, family and on the individual themselves. Background: This systematic review explored the use of interventions that could be used within practice to reduce the occurrences of disruptive vocalisation in people with dementia. Methods: Three online databases (CINAHL, MEDLINE and EMBASE) were searched for papers published after 1997 against two concept criteria of dementia and disruptive vocalisation. Any person diagnosed with dementia or suspected of having dementia symptoms were included identifying any interventions. Studies were appraised and data extracted using the Joanna Briggs Institute frameworks. Results: This systematic review identified eight relevant papers for inclusion, and these assessed the implementation of eight separate interventions that could be used within practice. Three interventions were found to be supported by statistically significant research: a staff training programme, a behavioural management technique using cue cards and hand massage. Conclusion: The overall conclusion is that the evidence base is insufficient to make recommendations for practice. However, the studies gave some indication of how research and practice might develop in this area. In particular, five elements were identified that appear to promote the best patient outcomes. These include making sure interventions are person‐centred, individualised, adaptable, with the use of multiple approaches, carried out by staff trained in the identification of disruptive vocalisation and ways to avoid triggering these behaviours. Implications for practice: Triggers which lead to older people with dementia expressing disruptive vocalisation should be identified. Multiple individualised interventions should be used to reduce the occurrences of the disruptive vocalisation.